Impacto de la pandemia en las ventas de la empresa distribuidora Touma S.A. durante el periodo 2020-2021. - Bajaña Valencia, Mary Dania (2022)
The Distribuidora Touma S.A with RUC number: 1290071700001 made in Ecuador, has a main office in the city of Babahoyo-Los Ríos located in Malecón 9 de octubre (Esq.), place of reference La carreta Restaurant, belongs to a franchisee of Disensa, it is of private nature. The present case study examined the IMPACT OF THE PANDEMIC ON THE SALES OF THE DISTRIBUTING COMPANY TOUMA S.A IN THE CITY OF BABAHOYO DURING THE PERIOD 2020-2021, has as main objective to analyze the performance of the company in times of pandemic of covid-19. We carry out comparisons of the total revenues for the periods 2020 and 2021, where we observe the variation of the same, for this we will propose possible solutions in order for the organization to know the reality in sales and its post-pandemic evolution. We will know the structure of the Distribuidora Touma SA with trade name DISENSA, who conform it in the administrative part and the person in charge of leading it in the commercial area. What were the beginnings of its commercial activity and how it happens to stay for several years in the competition, among other information.